Thermal and mechanical activation of inelastic events in metallic glasses. (1st March 2016) - Delogu, Francesco
Abstract: The activation-relaxation technique is used to explore the potential energy landscape of a Cu64 Zr36 metallic glass and to investigate how heating and elastic deformation affect the energy distribution of potential activations. It is shown that heating involves only a few low-energy activations, whereas stress-induced mechanisms are enabled by elastic deformation induce inelastic events over a broader energy range. Observed inelastic events exhibit features similar to those of STZs, which suggests a link between β relaxation and plastic deformation processes. Graphical abstract: